US State constitutional entrenchment and default in the 19th century. Issue 6 (7th August 2019) - Dove, John A.; Young, Andrew T.
Abstract: Constitutional scholars emphasize the importance of an enduring, stable constitutional order, which North and Weingast (1989) argue is consistent with credible commitments to sustainable fiscal policies. However, this view is controversial and has received little empirical study. We use 19 th -century US state-level data to estimate relationships between constitutional design and the likelihood of a government default. Results indicate that more entrenched and less specific constitutions are associated with a lower likelihood of default.